'Mangaldeep': Spreading Fragrance in India. (June 2016) - Sarmah, Bijoylaxmi; Rahman, Zillur
This case highlights Indian Tobacco Corporation (ITC)'s journey from being a pure leaf tobacco selling company to a reputed conglomerate with popular brands in diversified areas. ITC's corporate social responsibility (CSR) and sustainability activities taking a turning point with the company taking an immense interest in integrating societal problems in its company's policies and strategies. These transformations can be seen in almost all the business divisions of ITC. Mangaldeep division, an incense stick division is not an exception to this change. However, the authors are trying to analyze the activities of ITC–Mangaldeep Business unit from different perspectives such as CSR, sustainability and shared value initiatives. Considering the resource constraint and the demand to meet the societal needs, it will be quite interesting to know how both these two challenges are met by a conglomerate like ITC simultaneously in the days to come. The case uses both primary and secondary sources of information to develop this teaching case.